Cover Picture: Renewable absorbents for CO2 capture: from biomass to nature (Greenhouse Gas Sci Technol 4/2019). Issue 4 (12th August 2019) - He, Qingyao; Shi, Mingfei; Liang, Feihong; Xu, Lang; Ji, Long; Yan, Shuiping
Abstract : The cover image is based on the Review Renewable absorbents for CO2 capture: from biomass to nature by Qingyao He et al., https://doi.org/10.1002/ghg.1902 . Cover image © Feihong Liang.